Edible Electrochemistry: Food Materials Based Electrochemical Sensors. Issue 22 (7th August 2017) - Kim, Jayoung; Jeerapan, Itthipon; Ciui, Bianca; Hartel, Martin C.; Martin, Aida; Wang, Joseph
Abstract: This study demonstrates the first example of completely food‐based edible electrochemical sensors. The new edible composite electrodes consist of food materials and supplements serving as the edible conductor, corn, and olive oils as edible binders, vegetables as biocatalysts, and food‐based packing sleeves. These edible composite electrodes are systematically characterized for their attractive electrochemical properties, such as potential window, capacitance, redox activity using various electrochemical techniques. The sensing performance of the edible carbon composite electrodes compares favorably with that of "traditional" carbon paste electrodes. Well defined voltammetric detection of catechol, uric acid, ascorbic acid, dopamine, and acetaminophen is demonstrated, including sensitive measurements in simulated saliva, gastric fluid, and intestinal fluid. Furthermore, successful biosensing applications are realized by incorporating a mushroom and horseradish vegetable tissues with edible carbon pastes for imparting biocatalytic activity toward the biosensing of phenolic and peroxide compounds. The attractive sensing performance of the new edible sensors indicates considerable promise for physiological monitoring applications and for developing edible and ingestible devices for diverse biomedical applications. Abstract : This study first demonstrates the first example of edible electrochemical sensors made solely of food materials, offering digestive and innocuous platform. Various types of food materials are demonstrated and their electroanalytical behaviors are characterized. For biomedical monitoring applications, several (bio)markers are detected in artificial biofluids, indicating that the developed edible sensors can be expanded to monitor healthcare status following gastrointestinal tract.